Implementasi Kebijakan Ketahanan Pangan di Dinas Ketahanan Pangan Kolaka Utara (Studi Implementasi Model Grindle) - Waode Helvi Mei Hamka; Andi Nurhidayah; Nuryanti Mustari (STKIP Subang, 2026)
This study aims to analyze the implementation of food security policy at the FoodSecurity Office of North Kolaka Regency using Grindle’s policy implementationmodel. A qualitative descriptive approach was employed through in-depth interviewsand document analysis. The findings reveal that the policy content has been clearlyformulated in terms of objectives, target groups, benefits, activities, resources, andexpected changes. However, limitations in human resources, budget allocation, andsupporting infrastructure reduce policy effectiveness. From the implementationcontext perspective, multi-level actors are involved, but differences in interests, localpolitical dynamics, and socio-economic conditions influence program distribution.Although positive changes have emerged in priority villages—such as increasedhousehold food production and income diversification—the implementation has notyet been evenly distributed. Strengthening institutional coordination, increasingbudget support, and enhancing community empowerment are necessary to improvesustainable food security governance at the local level.